PENGEMBANGAN AURORA 3D PRESENTATION SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 1 RUMBIA - Muhammad Sholeh Muntasir; Ningrum Ningrum; Tiara Anggia Dewi (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
The problem in this study is that the learning media used in SMA Negeri 1 Rumbia are textbooks and worksheets while the use of LCD projectors and multimedia are rarely used. For example multimedia from Microsoft poer point that looks still simple and there are still shortcomings in terms of appearance and display design. From these problems the researchers conducted research to develop interactive learning media based on aurora 3D presentation. This research is a research and development (R&D) using ADDIE research model which has five stages in its development procedures, namely stage 1) Analysis, 2) Planning, 3) Development, 4) Implementation (Implementation), 5) Evaluation (Evaluation). The learning media was assessed as feasible by 2 media experts and 1 material expert. after the revision of learning media can be tested on a small group in class X IPS SMA Negeri 1 Rumbia, amounting to 28 students. The results of the assessment of learning media experts obtained a percentage of 93% with a very decent category. and The results of expert assessment of learning materials obtained a percentage of 94% with a very decent category. While the students' response to Aurora 3D Presentation as Interactive Learning Media shows a percentage of 90% with a very decent category. So it can be concluded that Aurora 3D Presentation as an Interactive Learning Media developed can be used in the learning process.